1994
DOI: 10.1063/1.166056
|View full text |Cite
|
Sign up to set email alerts
|

Equidistant spectra of anharmonic oscillators

Abstract: Some representative potentials of the anharmonic-oscillator type are constructed. Some corresponding spectra-shift operators are also constructed. These operators are a natural generalization of Fok creation and annihilation operators. The Schrodinger problem for these potentials leads to an equidistant energy spectrum for all excited states, which are separated from the ground state by an energy gap. The general properties of the dynamic system generated by spectral-shift operators of third degree are analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 4 publications
0
69
0
Order By: Relevance
“…We will see in this section that the difficulties in the analysis grow with the order of the PHA: for zeroth and first order the systems become the harmonic and radial oscillators respectively [4,47,49,50]. On the other hand, for second and third order PHA, the determination of the potentials reduces to find solutions of Painlevé IV and V equations, respectively [4,51].…”
Section: General Systems Ruled By Phamentioning
confidence: 99%
See 2 more Smart Citations
“…We will see in this section that the difficulties in the analysis grow with the order of the PHA: for zeroth and first order the systems become the harmonic and radial oscillators respectively [4,47,49,50]. On the other hand, for second and third order PHA, the determination of the potentials reduces to find solutions of Painlevé IV and V equations, respectively [4,51].…”
Section: General Systems Ruled By Phamentioning
confidence: 99%
“…The algebraic structure generated by {H, L − m , L + m } provides information about the spectrum of H, Sp(H) [6,19,47]. In fact, let us consider the mth-dimensional solution space of the differential equation…”
Section: Polynomial Heisenberg Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Subsequently, it has been shown that there are a number of exactly solvable potentials whose solutions are given in terms of these exceptional orthogonal polynomials ͑EOPs͒. 7 Here our objective is to re-examine some earlier results 8,9 related to conditionally exactly solvable potentials 10 in the context of EOPs, supersymmetry, and polynomial algebras. 4 The relation between EOPs, second order supersymmetry, 5 and shape invariance 6 has been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…It is important to note that general systems ruled by second-and third-order polynomial Heisenberg algebras, described by one-dimensional Schrödinger Hamiltonians having third and fourth-order differential ladder operators, are linked to the Painlevé IV and V equations respectively [30,[33][34][35][36][37][38][39][40][41][42][43]. This connection was exploited in [28] to generate solutions to the Painlevé IV equation, using the SUSY partner Hamiltonians for the truncated oscillator, where it was used that the initial system is ruled by the Heisenberg-Weyl algebra.…”
Section: Introductionmentioning
confidence: 99%